Spectrum sensing measurement using GNU radio & USRP software radio platform - Lo, A. C. C. (2011)
Spectrum utilization can be significantly improved by adopting cognitive radio (CR) technology. Such radios are able to sense the spectral environment and use this information to opportunistically provide wireless links that meet the user communications re quirements optimally. To achieve the goal of cognitive radio, it is a fundamental requirement that the cognitive user (CU) performs spectrum sensing to detect the presence of the primary user (PU) signal before a spectrum is accessed as to avoid harmful in terference. Therefore, two probabilities are of interest; the probability of detection, P d and the probability of false alarm, P fa . In this paper, we investigate sensing performance implemented on real -time testbed of GNU Radio and USRP Software Defined Radio (SDR) communi cation platform operating at 2.48 GHz with a bandwidth of 4 MHz. Energy detector utilizing 1024 FFT bin is the sensing mechanism used in the experimental set -up. The acquired experimental results of P d and P fa are duly analyzed and verifie d to be comparable to the curve of the theoretical framework for line -of-sight indoor environment. It is observed that at a target P fa of 5%, the optimal decision threshold for PU detection is -39 dB. The plot of measured number of samples needed for a des ired P d for various received signal levels, representing various signal -to-noise (SNR) conditions, is also included. At SNR of 0 dB and a target Quality of Service (QoS) set at P d of 90%, it is found out that the required sensing time for our GNU Radio USR P based CR system is equal to 31.59ms.